2017
DOI: 10.1016/j.biomaterials.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Essential design considerations for the resazurin reduction assay to noninvasively quantify cell expansion within perfused extracellular matrix scaffolds

Abstract: Precise measurement of cellularity within bioartificial tissues and extracellular matrix (ECM) scaffolds is necessary to augment rigorous characterization of cellular behavior, as accurate benchmarking of tissue function to cell number allows for comparison of data across experiments and between laboratories. Resazurin, a soluble dye that is reduced to highly fluorescent resorufin in proportion to the metabolic activity of a cell population, is a valuable, noninvasive tool to measure cell number. We investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 38 publications
1
67
0
1
Order By: Relevance
“…Based on the induction of γ-H 2 AX, indicative of DNA damage by some test compounds, their potential to transform substrate-dependent growth of HepG2 cells into substrate-independent cell growth by DNA mutations was assessed. To quantify transformation potential of our test compounds, a high throughput variant of the traditional semi-solid agar invasion assay was employed [ 33 ] using resorufin fluorescence as the indicator of cell growth [ 34 ]. The mutagenic compound 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) was used as a positive control [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the induction of γ-H 2 AX, indicative of DNA damage by some test compounds, their potential to transform substrate-dependent growth of HepG2 cells into substrate-independent cell growth by DNA mutations was assessed. To quantify transformation potential of our test compounds, a high throughput variant of the traditional semi-solid agar invasion assay was employed [ 33 ] using resorufin fluorescence as the indicator of cell growth [ 34 ]. The mutagenic compound 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) was used as a positive control [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The plates were left to solidify for 1 h at room temperature and incubated overnight at 37°C before cells were treated for 21 days with reference and test compounds (10–40 μM in 15 µL DMEM/well). Subsequently, the cells were stained with resazurin for 4 h (440 µM in 7 µL PBS/well) [ 34 ] before fluorescence (Ex/Em 545/600 nm) was quantified using a plate reader (Fluoroskan Ascent, Thermo Fisher Scientific, Scoresby, VIC, Australia). RFUs were standardized on the non-treated control and expressed as fold-induction.…”
Section: Methodsmentioning
confidence: 99%
“…matches findings by O'Brien et al (2000) and Chen et al (2018), who demonstrated that a secondary reaction from Rru to hydroresorufin is favored after all Raz has been reduced (reducing total detectable Raz + Rru) and that this reaction can happen both inside and outside cells. Another study using recellularized kidney scaffolds observed a fluorescence peak that gradually decreased throughout the assay, decaying to zero by 24 hr, demonstrating that cells were capable of secondary reduction of Rru to hydroresorufin (Uzarski et al, 2017). Moreover, Vehniäinen et al (2012) demonstrated that in the liver S9 fraction of some fish species, Rru was enzymatically reduced to a less fluorescent form.…”
Section: Anomalies In Recovery Time Series and Potential Drivers Of Imentioning
confidence: 99%
“…Cell viability was measured using a resazurin assay based on our previous protocol with some modifications (Uzarski, DiVito, Wertheim, & Miller, 2017). A 440 μM stock solution of resazurin sodium salt (Sigma Aldrich, St. Louis, MO) was prepared in PBS and then diluted 1 to 10 in fresh cell culture media for each cell type to create a working solution.…”
Section: Cell Proliferation and Viabilitymentioning
confidence: 99%